Enhancing Housekeeping Workforce Competency in the Hospitality Industry: A Comprehensive Training Approach - Hidajat, Benedictus Widjaya; Mansur, Ahmad (International Journal of Integrative Sciences, 2024)
This study examines the influence of comprehensive training programs on the proficiency of housekeeping personnel in the hotel sector. Data were collected through semi-structured interviews, focus group discussions, and participant observations at different hotels using a qualitative study approach. The findings suggest that organized training programs have a substantial impact on improving technical skills, such as proficiency in advanced cleaning procedures and equipment handling, as well as enhancing soft skills, such as effective communication and customer service. The integration of several learning methods, including simulation-based training and virtual reality, was discovered to be extremely successful in involving workers and enhancing the acquisition of skills. Although faced with obstacles such as reluctance to change and limited resources, the use of proactive solutions, such as engaging staff in training development and providing ongoing professional development, effectively addressed these concerns. The results emphasize the need of a comprehensive training strategy that encompasses both technical and soft skills in order to enhance overall service quality and operational efficiency. Suggestions for future practice including consistently refreshing training material, involving personnel in the development process, and overcoming obstacles to implementation in order to maintain increases in housekeeping performance and visitor satisfaction